2018
DOI: 10.5455/handmicrosurg.285986
|View full text |Cite
|
Sign up to set email alerts
|

A study of the radiographic morphometry of the distal radius in a south Indian population

Abstract: Background: Distal radius fractures are arguably the most common orthopedic injuries encountered by the treating orthopedic surgeon. Correction of dorsal tilt and radial height is important to restore the normal biomechanics of the wrist joint. The aim of this study is to report the morphometry of the distal radius in a South Indian population and give a comparison to similar studies of other races and populations. Methods: Three hundred and ten consecutive plain radiographs of the wrist joint were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 11 publications
(27 reference statements)
2
15
0
Order By: Relevance
“…Our findings are comparable to Hadi et al, 17 where he observed mean RH of 11.36±1.66 mm. Nekkanti et al 18 found small RH of 8.80±2.6mm in the south indian population. Our RH was slightly greater on both left and right side compared to Gupta et al 19 The mean PT in our study was 9 but is greater than Werner et al ie 6mm.…”
Section: Discussionmentioning
confidence: 92%
“…Our findings are comparable to Hadi et al, 17 where he observed mean RH of 11.36±1.66 mm. Nekkanti et al 18 found small RH of 8.80±2.6mm in the south indian population. Our RH was slightly greater on both left and right side compared to Gupta et al 19 The mean PT in our study was 9 but is greater than Werner et al ie 6mm.…”
Section: Discussionmentioning
confidence: 92%
“…Data were analyzed as a whole population and grouped between male and female gender, three different age groups(16-36 years, 37-57 years and > 57 years), and also compared to OTA reference value. 4,6…”
Section: Methodsmentioning
confidence: 99%
“…2 The distal radius includes the four important morphological parameters: palmar tilt (PT), radial inclination (RI), radial height (RH), and ulnar variance (UV) which are consequential in management of DRF, distal radius plate design and kinesiology. 3,4 The pressure distribution in the ulnar and radial articular surfaces changes in position and become more concentrated with increased PT. 4,5 Several researches recorded quite different value of it from the western literature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations